Working capital approaches and firm's returns in Pakistan - Talat Afza; Mian Sajid Nazir (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2008)
This study investigates the relationship between the aggressive/conservative working capital policies for seventeen industrial groups of public limited companies listed at Karachi Stock Exchange for a period of 1998-2003. The ordinary least square regression model has been used to investigate into the relationship of working capital approaches and the returns of firms. The study found significant differences among their working capital investment and financing policies across different industries. Moreover, these significant differences are remarkably stable over the period of six years. The aggressive investment working capital policies are accompanied by aggressive working capital financing policies. Finally, we found a negative relationship between the profitability measures of firms and degree of aggressiveness of working capital investment and financing policies. The study would contribute a better understanding of working capital management policies in an emerging market like Pakistan.
Keywords: 330; Working capital; Aggressive working capital policy; Aggressive financing policy